Histamine poisoning and control measures in fish and fishery products - Visciano, Pierina; Schirone, Maria; Tofalo, Rosanna; Suzzi, Giovanna (Frontiers in Microbiology, 2014)
Histamine poisoning is one of the most common form of intoxication caused by the ingestion of fish and fishery products. Cooking, canning or freezing cannot reduce the levels of histamine because this compound is heat stable. All humans are susceptible to histamine and its effects can be described as intolerance or intoxication depending on the severity of the symptoms. The amount of histamine in food, the individual sensitivity and the detoxification activity in human organism represent the main factors affecting the toxicological response in consumers. Histamine is the only biogenic amine with regulatory limits set by European Legislation, up to a maximum of 200 mg/kg in fresh fish and 400 mg/kg in fishery products treated by enzyme maturation in brine.